Effect of cytokine cerebroproteciton on the state of antioxidant thiol-disulfide system in the brain tissue of rats with experimental diabetes mellitus - Suprun, E; But, N; Suprun, A (Annals of Mechnikov's Institute, 2020)
Agents, providing both for damaging effect and cell viability system in the ischemia/hypoxia area, include cytokines – intercellular communication transmitters in health and disease, which establish communication signal network between cells of the immune system and cells of other organs and tissues. According to present day ideas, nature of immune response and peculiarities of development of the pathophysiological changes in ischemic/hypoxic tissue disorders depends on preemptive activation of the T-lymphocyte subpopulations, their synthesis of cytokines of various types and formation of "cytokine cascade", i.e. relation between pro-inflammatory and anti-inflammatory cytokines. Therefore, application of cytokine preparations may become effective perspective link in the complex therapy of port-ischemic complications in DM. In case of ischemic dmaage to the brain tissue in DM model, TDS balance shifts due to decrease in its reduced intermediates on the background of oxidized forms, with considerable lowering of reduced glutathione level and GR and GP activity. Similar pathological biochemical changes cause significant functional changes in cells and are often irreversible. Changes on TDS activity and oxidation of thiol groups of a cystein-dependent protein region of the mitochondrial internal membranes cause depolarization and destabilization of the mitochondrial internal membranes, with so called non-selective PT-pore (permeability transition pore – PTP) being formed. Opening of such channel in the internal membrane results in establishing ion balance in the matrix and mitochondrial intermembranous space, distributes hydrogen ion gradient (Н+) to the internal membrane and breaks respiratory chain. Also, this causes volume disregulation of mitochondria due to the matrix hyperosmolality, results in the increased matrix volume, breaks of the external membrane and growing destabilization of mitochondria and enzyme system, leads to development of persistent mitochondrial dysfunction, and as a result, to mitochondrial death – mitoptosis. Moreover, IL-1, produced in response to hypoxia, expresses inducible NOS (iNOS) in the glial cells, which results in NO hyperproduction and toxic effects die to its excessive amount. Excessive amount and its highly toxic derivatives nitrosylate proteinclinging enzymes of the respiratory chain of mitochondria and Krebs cycle, and inhibit them. Dysfunction of mitochondrial enzyme complexes (MEC) is formed, which causes qualitative changes of iron-sulfur centers in the mitochondrial enzymes and their functions, as well as suppression of a main (NADdependent) pathway for the substrate oxidation in respiratory chain. Aerobic energy synthesis is suppressed, thus bioenergetic (tissue) hypoxia is developed. Under conditions of the impaired generation of cell energy, caused by mitochondrial dysfunction, loss of NAD and ATP results in death of cells by necrosis or apoptosis. These pathophysiological changes form the basis of occurrence of early or late postischemic DM complications, resulting in disturbance of the usual lifestyle and lowering of life quality, persistent loss of occupational capacity and rapid progression of heavy neurological consequences up to lethal outcome. To gain maximum protective effect in the DM therapy, it is necessary to achieve interruption of pathogenetic ischemic/hypoxic cascade at earlier stages, which includes stage of thiol-disulfide imbalance establishing. Normalization of TDS state allows prevention of depolarization and destabilization of the mitochondrial internal membrane followed by development of mitochondrial dysfunction, energy imbalance and other post-ischemic consequences.